Cost utility analysis of endoscopic sinus surgery for chronic rhinosinusitis. Issue 6 (17th March 2016) - Scangas, George A.; Su, Brooke M.; Remenschneider, Aaron K.; Shrime, Mark G.; Metson, Ralph
Abstract : Background: The purpose of this work was to evaluate the cost‐effectiveness of endoscopic sinus surgery (ESS) compared to medical therapy for patients with chronic rhinosinusitis (CRS). Methods: The study design consisted of a microsimulation Markov decision‐tree economic model with a 31‐year time horizon. A cohort of 489 patients who underwent ESS for CRS were matched 1 to 1 with a cohort of 489 patients from the national Medical Expenditures Panel Survey database who underwent medical management for CRS. Utility scores were calculated from responses to the EuroQol 5‐Dimension instrument in both cohorts. Decision‐tree analysis and a subsequent 10‐state Markov model utilized published event probabilities as well as primary data from a large multisurgeon prospective outcomes study to calculate long‐term costs and utility. The primary outcome measure was incremental cost per quality‐adjusted life year (QALY). Multiple sensitivity analyses were performed. Results: The incremental cost‐effectiveness ratio (ICER) for ESS vs medical therapy alone was 13, 851.26 per QALY. The cost effectiveness acceptability curve demonstrated 85.84% and 98.69% certainty that the ESS strategy was the most cost‐effective option at willingness‐to‐pay thresholds of 25, 000 and 50, 000 per QALY, respectively. Conclusion: This study shows ESS to be a cost‐effective intervention compared to medical therapy alone for the management of patients with CRS.